USULAN PERBAIKAN FASILITAS KERJA PEMOTONGAN KABEL DIVISI CABLE CASING DI PT.INSERA - Anthony Teguh Setiawan; Hery Christian Palit; Juliana Anggono (Jurnal Titra, 2013)
The aim of this research is improving the work facility of cable cutting process at PT. InseraSena. The work facility for cable cutting process is not working effectively and it causes cleaning process that should not be needed. The second problem is the cable placement area is to big. Facility improvement which had been done is improvement of cutting tool of cable cutting process by using cutoff machine and design of cable placement shelf. As a result of facility improvement is cable cutting process which not requiring any cleaning are 96 from 100 cables. It is also decrease the average cutting time by 35%. Improvement of cable placement shelf resulting in a decrease of cable placement area which was 220 cm x 110 cm and now become 50 cm x 110 cm